Winter Weed Emergence during Carinata (Brassica carinata) Production - Ruby Tiwari; Pratap Devkota; Michael J. Mulvaney (EDIS, 2021)
This publication provides information for predicting emergence timing of common winter weed species for carinata production. Written by Ruby Tiwari, Pratap Devkota, and Michael J. Mulvaney, and published by the UF/IFAS Agronomy Department, June 2021.